Italy and Ethiopia: the Colonial Interlude Revisited - Sbacchi, Alberto (Aethiopica, 2004)
In 1997 the president of the Italian Republic visited Ethiopia and Eritrea to acknowledge the mistakes of Italian colonialism toward the people of the Horn of Africa. The theme of Italian colonialism in Ethiopia has long been an emotional one. However, in the last few years new archival resources have become available. The literature on the Italian occupation has become more objective and reliable. Hence there is a better appreciation of the Italian presence in Ethiopia, and the new generation is ready to admit Italy’s positive contribution. There are statistics on Italian investments in Ethiopia that show that Italy made the largest financial investment that Africa has ever seen. Considering those and other facts, the author of the paper attempts to reassess the issue of the Italian presence in Ethiopia, in all objectivity and on its own merits. ATTENTION: Due to copy-right no online publication is provided.